SUCCESSFUL MANAGEMENT OF UTERINE TORSION IN AN OSMANABADI GOAT - PATIL, A D (The Indian Journal of Animal Reproduction, 2020)
A five year old Osmanabadi goat was presented to the Obstetrical Ward, Teaching Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Udgir with the history of completion of gestational period. Animal was restless, dull, depressed with intermittent kidding signs. On per vaginal examination birth canal was dry and stenotic with a strong twist towards left side. The condition was diagnosed as left side post cervical uterine torsion (more than 1800). Detortion was performed by modified Schaffer’s method by using a hard wooden cart board with moderate palm pressure. Following correction, one dead male foetus was removed and the animal had an uneventful recovery. The present case report suggests that modified Schaffer’s method can be successfully performed for management of uterine torsion in a Osmanabadi goat.